2015
DOI: 10.1038/ncomms8903
|View full text |Cite|
|
Sign up to set email alerts
|

Elucidating the role of disorder and free-carrier recombination kinetics in CH3NH3PbI3 perovskite films

Abstract: Apart from broadband absorption of solar radiation, the performance of photovoltaic devices is governed by the density and mobility of photogenerated charge carriers. The latter parameters indicate how many free carriers move away from their origin, and how fast, before loss mechanisms such as carrier recombination occur. However, only lower bounds of these parameters are usually obtained. Here we independently determine both density and mobility of charge carriers in a perovskite film by the use of time-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
152
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(169 citation statements)
references
References 33 publications
14
152
2
1
Order By: Relevance
“…292,293 The solid points in Figure 28 (panels A and B) show Δσ 1 and Δσ 2 , respectively, for a room temperature CH 3 NH 3 PbI 3 thin film as measured by broadband TRTS. 291 The data clearly show characteristics of non-Drudian disordered transport. Fits to Δσ 1 and Δσ 2 (dashed lines) are therefore derived from a more general Drude-Smith model that accounts for carrier scattering, with contributions from Drude (yellow) and Smith (red) terms indicated.…”
Section: Optical Nonlinearity and Photoconductivitymentioning
confidence: 91%
“…292,293 The solid points in Figure 28 (panels A and B) show Δσ 1 and Δσ 2 , respectively, for a room temperature CH 3 NH 3 PbI 3 thin film as measured by broadband TRTS. 291 The data clearly show characteristics of non-Drudian disordered transport. Fits to Δσ 1 and Δσ 2 (dashed lines) are therefore derived from a more general Drude-Smith model that accounts for carrier scattering, with contributions from Drude (yellow) and Smith (red) terms indicated.…”
Section: Optical Nonlinearity and Photoconductivitymentioning
confidence: 91%
“…While a great deal of effort has been devoted to improving their efficiency 1,5,6 , our fundamental understanding of the crystalline and electronic structure phases, which are important for all electronic applications, is still lacking. Time-resolved terahertz (THz) spectroscopy experiments, for instance, have shown that at low temperatures, the large free-carrier density and mobility of CsPbBr 3 and MAPbI 3 make them ideal materials for charge-separation layers in photovoltaic cells 7 . However, the degradation of MAPbI 3 perovskites in air at high temperatures and with light illumination ultimately makes them unsuitable to be used in devices that would be exposed to constant light and heat 8 .…”
Section: Introductionmentioning
confidence: 99%
“…[22] Under such case, we can minimize the serious degradation of MAPbI 3 microplate devices over time to allow for a systematic investigation of the thermal annealing effect. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In particular, we have seen a rapid increase in the power conversion efficiency of perovskite solar cells to a certified efficiency higher than 20% in the past few years. However, due to the relative thick electrodes and uneven profile, the devices cannot be well encapsulated by BN, in which case the solvent used in device fabrication steps or moisture in air can reach the MAPbI 3 microplates along the electrodes, resulting in damaged microplates and poor device performance.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] In particular, we have seen a rapid increase in the power conversion efficiency of perovskite solar cells to a certified efficiency higher than 20% in the past few years. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In particular, we have seen a rapid increase in the power conversion efficiency of perovskite solar cells to a certified efficiency higher than 20% in the past few years.…”
mentioning
confidence: 99%